A Cross-Canada Surveillance of Antimicrobial Resistance in Respiratory Tract Pathogens. (1999) - Davidson, Ross J; Canadian Bacterial Surveillance Network,; Low, Donald E
Abstract : OBJECTIVE: To determine the prevalence of antimicrobial resistance in clinical isolates of Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis from medical centres across Canada. METHODS: Fifty laboratories from across Canada were asked to collect up to 25 consecutive clinical isolates of S pneumoniae, H influenzae and M catarrhalis at some time between September 1994 and May 1995, and then again between September and December of 1996. A total of 2364 S pneumoniae, 575 H influenzae and 200 M catarrhalis samples were collected. H influenzae and M catarrhalis isolates were tested for the production of beta-lactamase. S pneumoniae isolates were characterized as penicillin susceptible, intermediately resistant or high level penicillin-resistant. Minimal inhibitory concentrations (MICs) were determined using a microbroth dilution technique described by the National Committee of Clinical Laboratory Standards. RESULTS: Between the two collection periods, there was a significant increase in highly penicillin-resistant S pneumoniae from 2.1% to 4.4% (P<0.05) and an increase in intermediately penicillin-resistant strains from 6.4% to 8.9% (P<0.05). A significant increase in high level penicillin-resistant S pneumoniae was noted among paediatric isolates. No significant difference in the susceptibilities of comparator agents was detected. A significant increase in the number of beta-lactamase producing H influenzae, 34% to 43% (P<0.05) was observed. Ninety-five per cent of M catarrhalis isolates were beta-lactamase producers in both time periods. CONCLUSIONS: During the course of this study, the incidence of penicillin resistance in S pneumoniae doubled. As a result of this increase, infections due to this organism in sites where poor penetration of beta-lactam antibiotics occur may become increasingly difficult to manage.